From recognition to reconciliation : essays on the constitutional entrenchment of Aboriginal and treaty rights - Macklem, Patrick; Sanderson, Douglas, 1971- (University of Toronto Press, 2016)
In From Recognition to Reconciliation, twenty leading scholars reflect on the continuing transformation of the constitutional relationship between Indigenous peoples and the Canadian state.